PEMBELAJARAN SAINS PADA MATERI ORGAN GERAK HEWAN DAN MANUSIA SECARA DARING PADA SISWA KELAS V SD MENGGUNAKAN PENDEKATAN KONTEKSTUAL - Siti Nurhasanah Hidayat; Ryan Dwi Puspita (IKIP Siliwangi, 2022)
This research was conducted in class V SDN Ekaprasetia which aims to improve student learning outcomes which include the cognitive, affective and psychomotor domains on Sub-theme 1 Animal Movement Organs using a contextual approach. The condition of students who still do not understand the concept of the material being taught to achieve cognitive, affective and psychomotor learning outcomes causes student learning outcomes to be low and below the minimum completeness criteria (KKM). This is also caused by teachers who often use the lecture method and make learning seem monotonous, teachers also have not applied a contextual approach. This research uses descriptive research method. This research was conducted by doing online learning. The spread of the Covid 19 virus is very disruptive to learning in schools, distance learning or online is an alternative to learning at this time. The results showed the application of a contextual approach that was carried out online. Based on the results of the study, it can be concluded that the application of a contextual approach is effective in online learning on Sub-theme 1 Animal Movement Organs. Thus the contextual approach can be used as a model and method to be applied in classroom learning.